2017
DOI: 10.5812/ijp.5131
|View full text |Cite
|
Sign up to set email alerts
|

Shigellosis and Changes of Antimicrobial Susceptibility During Six Years

Abstract: Background: Shigellosis is a diarrheal disease caused by Shigella spp. The majority of cases and deaths occur among children less than 5 years old. In severe cases, antibiotic therapy is recommended to lessen the risk of serious complications and death. Prevalence of different Shigella species and their antibiotic resistance patterns are changing over the time. Objectives: The current study aimed at assessing the changes in the prevalence of Shigella species and their antibiotic susceptibility among 0-to 14-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…S. sonnei and S. flexneri are the most commonly isolated species in industrialized (23) and developing countries (24), respectively. In our study, S. sonnei was the most common cause of shigellosis, which is consistent with findings of other studies in Iran (25)(26)(27). Reasons behind the dominance of S. sonnei in industrialized countries remain unclear (28), but an increasing incidence of shigellosis caused by S. sonnei generally correlates with improving economic prosperity (29).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…S. sonnei and S. flexneri are the most commonly isolated species in industrialized (23) and developing countries (24), respectively. In our study, S. sonnei was the most common cause of shigellosis, which is consistent with findings of other studies in Iran (25)(26)(27). Reasons behind the dominance of S. sonnei in industrialized countries remain unclear (28), but an increasing incidence of shigellosis caused by S. sonnei generally correlates with improving economic prosperity (29).…”
Section: Discussionsupporting
confidence: 91%
“…However, more than 34% of Shigella isolates in our study were resistant and intermediately resistant to nalidixic acid. In a study by Ghavam et al in Iran, a similar frequency for resistance to nalidixic acid was observed (26), but in some countries higher resistance rates have been reported (7,31). Multi-drug resistance to the antimicrobial agents used for the treatment of shigellosis has been reported in many parts of the world (31,33,34).…”
Section: Discussionmentioning
confidence: 70%